ETIOTROPIC THERAPY OF VIRAL HEPATITIS - S. B. Chuelov; A. L. Rossina; V. F. Uchaikin (Детские инфекции (Москва))
Treatment of chronic viral hepatitis is not a fully resolved problem, especially in children. There are no convincing criteria for recovery. The paper presents various schemes used for etiotropic therapy of viral hepatitis at the present stage — interferons and antiviral drugs. For the treatment of hepatitis B, synthetic nucleoside and nucleotide analogues are used as an antiviral therapy, in the case of hepatitis C — ribavirin and protease and polymerase inhibitors. In children, interferon therapy remains important with the use of domestic drugs, including rectal forms of interferon administration (VIFERON®). At the same time, active research is underway to study non-interferon regimens for the treatment of chronic viral hepatitis in pediatric practice, but so far the choice of drugs for non-interferon therapy is limited to individual drugs. With hepatitis B, it is a lamivudine, prescribed from 3 years (the reception of which is accompanied by frequent development of resistance) and — tenofovir (appointed from 12 years). With hepatitis C, ribavirin can be administered from 3 years.